Physician preferences in using novel digital devices for the management of atrial fibrillation: a DAS-CAM III survey - Manninger-Wünscher, Martin; Zweiker, David; Hovakimyan, Tatevik; Matusik, Paweł T.; Conti, Sergio; Ollitrault, Pierre; Aro, Aapo; Mulder, Bart A.; Dichtl, Wolfgang; Heeger, Christian-Hendrik; ter Bekke, Rachel; Gul, Enes Elvin; et al. (Clinical cardiology, 2024)
Aim A recent European Heart Rhythm Association (EHRA) practical guide provides guidance on the use of novel digital devices for heart rhythm analysis using either electrocardiogram (ECG) or photoplethysmography (PPG) technology for the diagnosis of atrial fibrillation (AF). This survey assesses physicians' preferences to use digital devices in patients with possible AF and their impact on clinical decision-making. Methods and Results Participants of the DAS-CAM III initiated and distributed an online survey assessing physician preferences in using digital devices for the management of AF in different clinical scenarios. A total of 505 physicians (median age: 38 [IQR 33-46] years) from 30 countries completed the survey. A third of respondents were electrophysiologists, the others were cardiologists, cardiology residents, or general practitioners. Electrophysiologists were more likely to have experience with both ECG-based (92% vs. 68%, p < 0.001) and PPG-based (60% vs. 34%, p < 0.001) digital devices. The initial diagnostic approach to each scenario (symptomatic low-risk, symptomatic high-risk, or asymptomatic high-risk patient) was heterogeneous. Electrophysiologists preferred intermittent single-lead ECG monitoring to traditional Holter ECGs to screen for AF. Both electrophysiologists and non-electrophysiologists would rarely use PPG-based devices to diagnose and screen for AF (8.2%-9.8%). Electrophysiologists and non-electrophysiologists use ECG-based technology to confirm PPG-documented tracings suggestive of AF. Conclusion While PPG-based digital devices are rarely used for diagnosis and screening for AF, intermittent ECG-based digital devices are beginning to be implemented in clinical practice. More education on the potential of novel digital devices is required to achieve diagnostic pathways as suggested by the EHRA practical guide.